Disentangling the Attractiveness of Telework to Employees: A Factorial Survey Experiment - Eline Moens; Elsy Verhofstadt; Luc Van Ootegem; Stijn Baert (Institute of Labor Economics (IZA), 2022)
This research adds to the literature on the attractiveness of telework to employees. To this end, we set up an innovative factorial survey experiment in which a high-quality sample of employees evaluates job offers with diverging characteristics, among which a wide variation in telework possibilities. We find that the relationship between the possibility to telework and job attractiveness is approximately linear: 10 percentage points more telework hours yield a rise of 2.2 percentage points in job attractiveness and, therefore, the willingness to give up an increase of 2.3 percentage points in wage in the new job. Our experimental design also allows us to investigate the underlying mechanisms of this relationship as well as its moderators. We find that the attractiveness of telework is particularly explained by expectations of an improved work-life balance, more work scheduling autonomy, a higher job satisfaction, and more work methods autonomy in jobs with a greater possibility to telework. In addition, our analyses show that less conscientious employees are on average more attracted to jobs with greater telework possibilities, so that it is important that self-selection in jobs with more telework is well-monitored.
Keywords: J24; J81; J31; J63; I31; 330; telework; job attractiveness; factorial survey experiment